Development of a Process Based Data Driven Engineering Design Knowledge Reuse System. - Baxter, David; Gao, James X. (Cad Solutions, 2006)
This paper will describe the development of the web enabled version of a process based engineering design knowledge reuse system. The rationale for using the design process as a central element of knowledge management will be discussed. The system structure will be described. Evaluation of the prototype showed the most valuable attributes of system. Mapping the design process helped to create the product data model. Workshops were used to validate the system. A small number of product parameters are required for developing the product concept in the early stages. The research showed the importance of multi view validation and iteration in system development. It also showed the importance of graphics in design support. Key issues include: the importance of process capture, data model validation, the use of graphics in the interface, system design and system assessment.
Keywords: Design Knowledge Management; Design Reuse; Process Representation